Psychological trauma and its relationship to some variables among Secondary school students - Hussain, Ikhlas Ali (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to measure through a predictive study of a measure of the painful personal experience of university students. Ten goals were formulated, including building a two-dimensional traumatic personal experience scale, measuring the painful personal experience of university students, evaluating its statistical significance, measuring cognitive control among university students, and evaluating its statistical significance. Measuring the circumvention of university students and estimating the significance of statistical recognition of differences in personal experience. Pain is two-dimensional according to the variables of sex, age, and marital status and assessing its statistical significance. The research sample reached 293 students who underwent the psychometric characteristics of the scale, divided into two areas of cognitive control and avoidance, after extracting the psychometric characteristics using factor and exploratory analysis and confirmatory factor analysis.